2012
DOI: 10.1002/met.1291
|View full text |Cite
|
Sign up to set email alerts
|

Characterizing North Atlantic weather patterns for climate‐optimal aircraft routing

Abstract: Daily weather patterns over the North Atlantic are classified into relevant types: typical weather patterns that may characterize the range of climate impacts from aviation in this region, for both summer and winter. The motivation is to provide a set of weather types to facilitate an investigation of climate-optimal aircraft routing of trans-Atlantic flights (minimizing the climate impact on a flight-by-flight basis). Using the New York to London route as an example, the time-optimal route times are shown to … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

4
70
0

Year Published

2012
2012
2018
2018

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 52 publications
(74 citation statements)
references
References 24 publications
4
70
0
Order By: Relevance
“…Sridhar et al (2014) simulated the wind-optimal flight trajectory from Newark (EWR) to Frankfurt (FRA) using a specific winter day, and the flight time was 22 980 s. The flight time of the time-optimal flight trajectory from JFK to FRA simulated by AirTraf was 22 955 s. This agrees well with the value reported by Sridhar et al (2014). Irvine et al (2013) analyzed the variation in flight time of time-optimal flight trajectories between JFK and London (LHR) using weather data for three winters. The results showed that the flight time for eastbound and westbound flights ranged from approximately 18 000 to 22 200 s, and from 21 600 to 27 000 s, respectively (see Fig.…”
Section: Verification Of the Airtraf Simulationssupporting
confidence: 78%
See 2 more Smart Citations
“…Sridhar et al (2014) simulated the wind-optimal flight trajectory from Newark (EWR) to Frankfurt (FRA) using a specific winter day, and the flight time was 22 980 s. The flight time of the time-optimal flight trajectory from JFK to FRA simulated by AirTraf was 22 955 s. This agrees well with the value reported by Sridhar et al (2014). Irvine et al (2013) analyzed the variation in flight time of time-optimal flight trajectories between JFK and London (LHR) using weather data for three winters. The results showed that the flight time for eastbound and westbound flights ranged from approximately 18 000 to 22 200 s, and from 21 600 to 27 000 s, respectively (see Fig.…”
Section: Verification Of the Airtraf Simulationssupporting
confidence: 78%
“…The results showed that the flight time for eastbound and westbound flights ranged from approximately 18 000 to 22 200 s, and from 21 600 to 27 000 s, respectively (see Fig. 3 in Irvine et al, 2013). In addition, Grewe et al (2014a) optimized the trans-Atlantic 1-day air traffic (for winter) with respect to air traffic climate impacts and economic costs to investigate routing options for minimizing the impacts.…”
Section: Verification Of the Airtraf Simulationsmentioning
confidence: 99%
See 1 more Smart Citation
“…It contains the majority of transatlantic traffic, as indicated by gridded global inventories of fuel burn and emissions obtained from the Federal Aviation Administration's Aviation Environment Design Tool (Kim et al, 2005;Malwitz et al, 2005;Wilkerson et al, 2010;Wilcox et al, 2012). The altitude is chosen because it is within the range of permitted flight levels for the North Atlantic flight corridor (Irvine et al, 2013). According to a special report by the Intergovernmental Panel on Climate Change, the cruising altitudes of civil aircraft are not expected to increase significantly over the next few decades, because of physical limitations and costs (Penner et al, 1999, Section 7.2…”
Section: Methodology and Resultsmentioning
confidence: 99%
“…Compiled inventories of aircraft movement often use great circle routes (or assume a simple distribution around them) to approximate true aircraft routes; more recent inventories use radar data where available but must still use great circle routes over areas such as the North Atlantic where there is no radar coverage [Owen et al,2010;Wilkerson et al, 2010]. Aircraft routes over the North Atlantic vary greatly from day-to-day depending on the strength of the jet stream, and eastbound and westbound routes can differ significantly [Irvine et al, 2012]; in Section 3.3 it is demonstrated how this may introduce an error into estimates of contrail coverage which use great circle routes.…”
Section: Introductionmentioning
confidence: 99%